Diagnostic value of sacroiliac joint scintigraphy with 99m technetium pyrophosphate in sacroiliitis. - Berghs, H (1978)
Using a quantitative method, scintigraphy of SI joints was performed by means of 99m technetium pyrophosphate in 21 patients with definite ankylosing spondylitis, in 17 control patients, and in 26 patients 'at risk', i.e. patients with complaints of back pain of the inflammatory type where on clinical grounds there was a possibility of sacroiliitis developing but with normal x-ray findings of the SI joints. Radioisotope uptake was higher in the ankylosing spondylitis group than in the other two groups, although the difference was not statistically significant with regard to the group 'at risk'. The high variance in the three groups considerably reduces the diagnostic value of the examination. In the ankylosing spondylitis group no correlation was found between radioisotope uptake and age, duration of disease, erythrocyte sedimentation rate, or radiological stage of scaroiliitis. Since the specificity and sensitivity of scintiscanning are lower than that of clinical and radiological diagnosis of the disease, we conclude that scintigraphy is not very helpful in the early diagnosis of sacroiliitis, at least by the techniques used here.